Examination of MMPI–2–RF Substantive Scales as Indicators of Acute Suicidal Affective Disturbance Components. Issue 4 (4th July 2017) - Rogers, Megan L.; Anestis, Joye C.; Harrop, Tiffany M.; Schneider, Matthew; Bender, Theodore W.; Ringer, Fallon B.; Joiner, Thomas E.
ABSTRACT: A new suicide-specific diagnostic entity, acute suicidal affective disturbance (ASAD), was recently proposed to fill a void in the nomenclature. Although several studies have examined the reliability, validity, and potential clinical utility of ASAD, no studies have examined personality indicators of ASAD. This study sought to examine the association between personality and psychopathology factors, as assessed by the Minnesota Multiphasic Personality Inventory–2–Revised Form (MMPI–2–RF), and constructs that comprise ASAD in a sample of 554 psychiatric outpatients who completed all measures prior to their intake appointments. A smaller subset of patients ( N = 58) also completed a measure designed to assess lifetime ASAD symptoms. Results indicated that ASAD symptoms were associated with traits characterized by emotional turmoil and atypical cognitive processes. Further, suicide-related criteria that comprise ASAD were related to low positive emotionality and hopelessness, whereas the overarousal criteria were associated with somatic symptoms and an inability to tolerate frustration and stress. These findings expand on previous research that examines the convergent and discriminant validity of ASAD and could inform clinical treatment by providing insight into personality traits that might be associated with acute suicide risk.